Future of keeping pet reptiles and amphibians: animal welfare and public health perspective. (28th October 2017) - Warwick, C.; Jessop, M.; Arena, P.; Pliny, A.; Nicholas, E.; Lambiris, A.
Abstract : In a review summary on page 450, Pasmans and others discuss the future of keeping reptiles and amphibians as pets. Here, Clifford Warwick and others discuss the animal welfare and public health implications of exotic pet business.